PERUBAHAN LAHAN PERTANIAN TERHADAP KONDISI SOSIAL, EKONOMI DAN EKOLOGIS DI DESA LAKSANAMEKAR PADALARANG BANDUNG BARAT - A. Hadian Pratama Hamzah; Suratni; Nurhasanah (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2022)
Regional development and growth with the expansion of a village and a district encourage an increase which results in a significant increase in the utilization of land resources. This condition is the impetus for land exploration activities in the agricultural environment for industrial, residential and office use. This study seeks to find findings on the impact of land change and the factors that trigger agricultural land exploration. This research was conducted on 52 respondents who use agricultural areas in Laksanamekar Padalarang Village, West Bandung, with a time range from January to August 2021. Data processing was carried out using qualitative methods to see the effects of land exploration and quantitative methods through path analysis to see the relationship between variables on excessive use of agricultural land. The results showed that changes in physical environmental conditions resulted in a reduction in the area of paddy fields. Reduction of garden area, decrease in water quantity and quality. As a result of agricultural land exploration on social and environmental conditions, namely the emergence of business opportunities, there is a change of livelihood, increased income, increased lifestyle and the fading culture of cooperation. As much as 60.2% significant influence from government policy factors, population growth factors, economic factors, external factors and the existence of private investment on land changes in the environment of Laksanamekar Village, Padalarang, West Bandung regency.